THE PREVALENCE OF TRADITIONAL CARDIOVASCULAR RISK FACTORS, SUBCLINICAL CAROTID ATHEROSCLEROSIS, CORONARY ARTERY CALCIFICATION IN PATIENTS WITH EARLY PSORIATIC ARTHRITIS (A REMARCA STUDY - E. I. Markelova; D. S. Novikova; T. V. Korotaeva; E. Yu. Loginova; I. G. Kirillova (Научно-практическая ревматология, 2018)
Cardiovascular events (CVEs) are one of the most common causes of death in patients with psoriatic arthritis (PsA). The increased risk of CVEs in PsA is due to a combination of traditional cardiovascular risk factors (TCVRFs) and common inflammatory mechanisms underlying PsA and atherosclerosis.Objective: to estimate the prevalence of TCVRFs, subclinical atherosclerosis, and coronary artery calcification in young patients with early peripheral PsA.Subjects and methods. The investigation enrolled 25 patients (13 men, 12 women) with early PsA, who had participated in the REMARCA study. Their median age was 36 [27; 46] years; the duration of PsA and psoriasis was 5 [3; 7] and 13 [9; 84] months, respectively; DAS was 3.8 [3.4; 5.4].All the patients underwent assessment of TCVRFs, Doppler ultrasound (DUS) of the carotid arteries (CA), evaluation of CA calcification (CAC) using multislice computed tomography (MSCT) and echocardiography, as well as 24-hour blood pressure monitoring.Results and discussion. The patients with early PsA were found to have the following TCVRFs: hypertension in 11 (44%), abdominal obesity in 14 (56%), smoking in 16 (64%), a family history of cardiovascular disease in 6 (24%), menopause in 5 (20%), and dyslipidemia in 14 (56%). There was one TCVRF in 7 (28%), two TCVRFs in 6 (24%), three TCVRFs in 2 (8%), four TCVRFs in 4 (16%), and five TCVRFs in 6 (24%). A combination of three or more TCVRFs was found in 12 (48%) patients.Calculation of ten-year total coronary risk scores identified low [17 (68%)], moderate [6 (24%)], high [1 (4%)], and very high [1 (4%)] risk groups among the patients with a history of acute cerebrovascular accident. Analysis of the relationship between PsA activity and total coronary risk scores revealed no significant differences. Thus, the patients with moderate PsA activity showed low, moderate, and high coronary risks in 7 (70%), 2 (20%), and 1 (10%) cases, respectively.Those with high PsA activity had low, moderate, high, and very high risks in 10 (66.7%), 4 (26.6%), and 1 (6.7%) cases, respectively. CA DUS revealed atherosclerotic plaques (ASPs) in 8 (32%) patients and increased CA intima-media thickness (IMT) values of >0.9 mm in 8 (32%). MSCT showed signs of CAC in 4 (16%) patients. There was a correlation of IMT values with low-density lipoprotein (r = 0.48; p = 0.03), total cholesterol (r = 0.53; p = 0.01), systolic blood pressure levels (r = 0.59; p = 0.02), and abdominal obesity (r = 0.64; p = 0.001) and an inverse correlation between high-density lipoproteins and C-reactive protein levels (r = -0.52; p = 0.03).Young patients with PsA with early-stage disease have a high prevalence of TCVRFs, CA atherosclerotic changes, and CAC signs with relatively low total coronary risk scores, which may indirectly suggest that chronic inflammation is involved in the development of atherosclerosis.